Persepsi Masyarakat tentang Pencemaran Lingkungan di RW 009 Pejaten Timur - Fanny Irna Rachman; Dwinda Annisa; Rosita Sari; Angela Angela; Bayu Wicaksono (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
Environmental pollution, particularly river pollution caused by household waste, has become a major issue in densely populated residential areas. This condition is also found in RW 009 Pejaten Timur, where environmental quality has declined due to population growth, increasing domestic activities, and improper waste management practices. This study aims to examine community perceptions of environmental pollution in RW 009 Pejaten Timur, including the level of public knowledge, attitudes, and the factors influencing their perceptions of environmental conditions. This study employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the community is aware of the deterioration in environmental quality, particularly river pollution resulting from household waste and the practice of disposing of garbage into the river. However, this awareness has not been fully translated into environmentally responsible behavior due to practical considerations and the limited availability of household organic waste management facilities. Furthermore, the implementation of a biopore program is perceived as a promising initiative to reduce environmental pollution, provided that it is supported by active community participation. The study implies that improving environmental awareness should be accompanied by continuous environmental education, adequate waste management facilities, and collaboration among the community, local authorities, and government to achieve sustainable environmental management.